Panicle characters and yield capacity in rice (Oryza sativa) - GOVINDARASU, R; MANIAN, k; RAMAMOORTHI, N; HANIFA, A MOHAMED (The Indian Journal of Agricultural Sciences, 2013)
An investigation was carried out in rice (Oryza sativa L.) to study the components of yield sink capacity; Among 17 component characters analysed by correlation study, spikelets, grains, high density grains/panicle, secondary branches/ panicle, spikelets, grains and high density grains on secondary branches were found to be important contributing characters for grain, yield/panicle. The varieties which registered high values for these traits also recorded higher grain Yield/panicle. ’ Inter-correlation among these important contributing characters indicated strong correlation among themeselves suggesting simultaneous improvement of these characters through a simple selection. The study suggests that while handling a large germplasm or segregating populations by the breeders, secondary branches/panicle may be used as a criteria for selection for higher grain yield in rice, as recording of this character is simple and easy compared with other contributing characters.